2013
DOI: 10.1136/bmjopen-2013-002594
|View full text |Cite
|
Sign up to set email alerts
|

Medicines information needs during pregnancy: a multinational comparison

Abstract: ObjectivesThe aim was to assess the perceived needs of medicines information and information sources for pregnant women in various countries.DesignCross-sectional internet-based study.SettingMultinational.ParticipantsPregnant women and women with children less than 25 weeks.Primary and secondary outcome measuresThe need for information about medicines was assessed by a question: ‘Did you need information about medicines during the course of your pregnancy?’ A list of commonly used sources of information was gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
67
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 20 publications
10
67
0
4
Order By: Relevance
“…The importance of exploring information needs of pregnant women has attracted attention of governments and many researchers (Cronin, 2003;H€ ameen-Anttila et al, 2013;Herrel et al, 2004;Malata & Chirwa, 2011;Mooko, 2006;Ogunmodede et al, 2013). Identifying and considering women needs in the development of educational plans enables women to function more effectively in their responsibilities.…”
mentioning
confidence: 99%
“…The importance of exploring information needs of pregnant women has attracted attention of governments and many researchers (Cronin, 2003;H€ ameen-Anttila et al, 2013;Herrel et al, 2004;Malata & Chirwa, 2011;Mooko, 2006;Ogunmodede et al, 2013). Identifying and considering women needs in the development of educational plans enables women to function more effectively in their responsibilities.…”
mentioning
confidence: 99%
“…Ventajas Se ha demostrado que los recordatorios de correo electrónico tienen un efecto positivo en el número de nuevas visitas web y se sugirieron como una estrategia para retener al paciente 39 .…”
Section: Ventajas Y Desventajas Del Uso De Tic En Obstetriciaunclassified
“…Accordingly, pregnant women are in need of adequate information from health care professionals. In a recent study, 57% of the women reported a need for information about medicines during pregnancy, citing physicians (73%), the internet (60%) and pharmacy personnel (46%) as the three most commonly used information sources (Hämeen-Anttila et al, 2013). However, very few studies have investigated pharmacists' counselling of pregnant women (Appendix 1).…”
Section: Introductionmentioning
confidence: 99%